Distribution and variation in proteins of casein micellar fractions response to heat-treatment from five dairy species. (15th December 2021) - Han, Rongwei; Shi, Runjia; Yu, Zhongna; Ho, Harvey; Du, Qijing; Sun, Xueheng; Wang, Jun; Jiang, Hongning; Fan, Rongbo; Yang, Yongxin
Highlights: Changes in proteins of casein micelles induced by heat treatment were detected by LC-MS. Changes in lipoprotein lipase and α-lactalbumin of casein micelle induced by heat treatment were similar among the studied species. Variation in proteome of casein micelles related to the intensity of heat treatment observed in the specific type of milk. Different abundant proteins related to function and pathway were varied among the studied species. Abstract: Casein micelles (CMs) contribute to the physicochemical properties and stability of milk. However, how the proteome of CMs changes following heat treatment has not been elucidated. Here, changes in the proteins of CMs in samples of Holstein, buffalo, yak, goat, and camel milk following heat treatment were investigated using a LC-MS/MS approach. According to the hierarchical clustering results, Holstein, yak, and buffalo milk samples had similar CMs protein components, followed by goat and camel milk samples. Changes in lipoprotein lipase and α-lactalbumin in CMs were dependent on the intensity of heat treatment and were similar among the studied species, whereas changes in κ-casein, lactoferrin, and apolipoprotein A-I differed among different types of milk. These results provide information on the distribution and variations of the proteomes of CMs following heat treatment, which will assist in the identification of proteins that are dissociated and attached to CMs from different dairy species during heat treatment.